The Nigerian economy under the military - Kayode, Femi.; Ajayi, Ibi.; Nigerian Economic Society (Kano : Nigerian Economic Society, 1980)
The papers in the proceedings reflect the authors' view of the management/performance of the economy. The contributors have been drawn from a fairly representative cross-section of the society including academics, businessmen, civil servants, etc. The coverage of the papers are extremely broad and include Management of the Economy, Nigerian Economic Policy, Appraisal of Agricultural Policy, Fiscal Processes and Income Distribution, Industrial Policy, Anti-Inflation Policies, Export Policy etc. It is hoped that the lessons learnt would be beneficial to all and in particular it will guide the civilian regime in the formation, execution of accurate and efficient economic policy for the future.
Proceedings of the 1980 annual conference of the Nigerian Economic Society.
Includes bibliographical references.
Ref
rpm 14/12/2017
Keywords: Nigeria $1 (BEconomic conditions.s; Military government; Nigeria